2017
DOI: 10.1515/mjss-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Political Connections on the Firm Performance in a Newly Democratised Country

Abstract: The study of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 18 publications
1
29
3
Order By: Relevance
“…We hardly find similar studies in other country, which have different characteristics from China. As far as we know there are only research from Saeed et al (2016) in developing country using sample from Pakistan, and research taken from democratic country of Tunisia by Bencheikh and Taktak (2017), which mainly talked about political connections and firm performance. So we address this research gap to examine the relationship between political connections and overinvestment in a developing, democratic and multi-party country.…”
Section: Introductionmentioning
confidence: 99%
“…We hardly find similar studies in other country, which have different characteristics from China. As far as we know there are only research from Saeed et al (2016) in developing country using sample from Pakistan, and research taken from democratic country of Tunisia by Bencheikh and Taktak (2017), which mainly talked about political connections and firm performance. So we address this research gap to examine the relationship between political connections and overinvestment in a developing, democratic and multi-party country.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, under stakeholder theory, there are reciprocal benefits to be connected with the politicians, the connected firms are expected to gain benefits to maximize stakeholders' wealth, at the same time they bear the costs according to contributing to politicians' campaigns and the achievement of their electoral programs (Cooper et al, 2010;Tahoun, 2014). Accordingly, considering politicians rent extractions, improvement in the firm value will happen if the marginal benefits of the PCs outweigh their marginal costs (Shleifer and Vishny, 1994;Faccio, 2006;Bencheikh and Taktak, 2017). For example, Bertrand et al (2018) found that politically connected firms in France are less profitable compared to unconnected firms, especially in politically contested areas and in election years.…”
Section: Research Hypothesis Developmentmentioning
confidence: 99%
“…Specifically, some unobserved factors of profitability and firm's market value may also explain PCs, leading OLS estimates to be inconsistent and biased. Depending on the 2SLS method, three instrumental variables as well as the other independent variables regressing in the first stage of the 2SLS method to estimate the different types of PCs, these variables are, firm age, which measured as a natural logarithm of firm age (Boubakri et al, 2012b;Bencheikh and Taktak, 2017), lagged of market capitalization (Lag MC) which is calculated as multiplying the number of shares outstanding by the share price at year-end (Faccio et al, 2006;Goldman et al, 2009;Maaloul et al, 2018) and lagged return on assets (Lag ROA) (Maaloul et al, 2018), then the fitted values for different PCs types are used in the second stage of OLS regression. Results show similar results to the main results of the OLS regression (results reported in Table 9).…”
Section: Endogeneity Testmentioning
confidence: 99%
“…According to Huang and Zhao (2016), political connections can be a positive correlation against the CSR performance of private companies listed on the Shanghai Stock Exchange for the period 2008-2014. In addition, political connections are considered capable of giving advantages to improve the company's performance (Bencheikh, et al, 2017) and also increase the value of the company (Faccio, 2006). Therefore, the second hypothesis in this research is as follows:…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%